Effects of High-Temperature Stress during Plant Cultivation on Tomato (Solanum lycopersicum L.) Fruit Nutrient Content - Dasgan, Hayriye Yildiz; Dere, Sultan; Akhoundnejad, Yelderem; Arpaci, Bekir Bulent (Wiley, 2021)
Agriculture is among the sectors that will be impacted first and most by the adverse effects of climate change. Therefore, developing new high-temperature tolerant varieties is an essential economic measure in adaptation to near-future climate change. Likewise, there is a growing interest in increasing the antioxidant content of crops to improve food quality and produce crops with high-stress tolerance. Tomato is the most grown and consumed species in horticultural plants; however, it is vulnerable to 35 degrees C and above high temperatures during cultivation. This study used twenty high-temperature tolerant, two susceptible genotypes, and two commercial tomato varieties in the open field. The experiment was applied under control and high-temperature stress conditions based on a randomized block design with 4 replications and 12 plants per repetition. The study investigated the fruit's selected quality properties and antioxidant compounds, namely, total soluble solutes (Brix), titratable acidity, pH, electrical conductivity (EC), lycopene, beta-carotene, and vitamin C, along with total phenols and total flavonoids under control and stress conditions. As a result, in general, total soluble solutes, titratable acidity, total phenol, and vitamin C contents under high-temperature conditions were determined to increase in tolerant tomato genotypes, while decreases were noted for pH, EC, total flavonoids, lycopene, and beta-carotene. However, different specific responses on the basis of genotypes and useful information for breeding studies have been identified. These data on fruit nutrient content and antioxidants will be helpful when breeding tomato varieties to be grown in high-temperature conditions.